The Influence of Flipped Classroom-Based Project Assessment on Concept Understanding and Critical Thinking Skills in Physics Learning - Rapi, N. K.; Suastra, I. W.; Widiarini, P.; Widiana, I. W. (Jurnal Pendidikan IPA Indonesia, 2022)
This study aims to analyze the influence of flipped classroom-based project assessment on critical thinking skills and physics learning outcomes. This quantitative research has a post-test-only non-equivalent control group design. The population is distributed into two classes. The data are collected using questionnaires and tests and analyzed using descriptive statistics and Manova. The results indicate differences between critical thinking skills and physics learning outcomes between students who learned with project assessments based on the flipped classroom approach and students who learned with conventional assessments simultaneously and partially. The significance value indicates more than 0.05. Thus, it can be concluded that flipped classroom-based project assessment influences critical thinking skills and concept understanding. Flipped classroom-based project assessment is recommended as one innovative assessment based on constructivism to improve concept understanding and critical thinking. Excellent critical thinking skills and concept understanding will help students solve contextual problems.